Combining charge density analysis with machine learning tools to investigate the Cruzain inhibition mechanism - Luchi, Adriano Martín (2019)
Fil: Luchi, Adriano Martín. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.